2019
DOI: 10.3389/fpsyg.2019.01333
|View full text |Cite
|
Sign up to set email alerts
|

Self-Concept and Physical Activity: Differences Between High School and University Students in Spain and Portugal

Abstract: The period of adolescence stands out as a critical and decisive phase, first because it leaves its mark on personality development, which is affected by psychosocial factors, and second because the healthy lifestyle habits acquired during this stage form a foundation for adulthood. The objective of the present study was first to evaluate the levels of participation in physical activities (PA) and of self-concept in high school and university students, and second to find relationships between these psycho-physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 50 publications
1
20
0
6
Order By: Relevance
“…The scale comprises thirty items, six per dimension, with a response scale ranging from 1 to 99. AF5 is one of the most widely used measuring instruments for self-concept among Spanish-speaking samples (e.g., Lila et al, 2000;Pellerano et al, 2006;Méndez-Giménez et al, 2013;González-Hernández, 2017, 2018;Onetti-Onetti et al, 2019). The structure of the scale has been empirically tested using exploratory factorial analysis (García and Musitu, 2014) and confirmatory factorial analysis (García et al, 2006(García et al, , 2011).…”
Section: Physical Self-conceptmentioning
confidence: 99%
“…The scale comprises thirty items, six per dimension, with a response scale ranging from 1 to 99. AF5 is one of the most widely used measuring instruments for self-concept among Spanish-speaking samples (e.g., Lila et al, 2000;Pellerano et al, 2006;Méndez-Giménez et al, 2013;González-Hernández, 2017, 2018;Onetti-Onetti et al, 2019). The structure of the scale has been empirically tested using exploratory factorial analysis (García and Musitu, 2014) and confirmatory factorial analysis (García et al, 2006(García et al, , 2011).…”
Section: Physical Self-conceptmentioning
confidence: 99%
“…The need to study the association between self-concept and physical activity during this period lies in the importance of children's development, with the physical practice being a means of improving mental processes and socialisation in children [19]. Adolescents who habitually participate in physical and sports activities have a better self-concept, which is the social motor that drives better academic performance and helps their relations with peers [24].…”
Section: Introductionmentioning
confidence: 99%
“…The average validated PA of students in sports and fitness is 274 minutes per week (about 39 minutes per day). It should be recognized that this data is below the level PA recommended by experts for maintaining physical health (60 minutes per day) [5].…”
Section: Discussionmentioning
confidence: 60%
“…The lack of regular PA is the main threat to the development of obesity in modern youth and students [3]. It was found that a significant percentage of university students do not follow the recommendations for performing a certain volume of PA during the day (60 minutes of moderate PA) [4], and the week (150 minutes of vigorous PA) [5]. It is known that the transition from school to university is accompanied by a decrease in motor activity, an increase in a sedentary lifestyle and the development of the risk of obesity in young people [6].…”
mentioning
confidence: 99%